2017
DOI: 10.1021/acschemneuro.6b00376
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis and in Vivo Evaluation of [11C]A1070722, a High Affinity GSK-3 PET Tracer in Primate Brain

Abstract: Dysfunction of glycogen synthase kinase 3 (GSK-3) is implicated in the etiology of Alzheimer’s disease, Parkinson’s disease, diabetes, pain, and cancer. A radiotracer for functional positron emission tomography (PET) imaging could be used to study the kinase in brain disorders and to facilitate the development of small molecule inhibitors of GSK-3 for treatment. At present, there is no target-specific or validated PET tracer available for the in vivo monitoring of GSK-3. We radiolabeled the small molecule inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Another potent GSK-3 inhibitor, A-107 (Ki=0.6 nM for GSKα and GSK-3β) (59), was selected for the study. OA followed by A-107 treatment showed 23% reduction of 110 kDa oligomeric form band (CP13) and non-significant but partial reduction of the 240 kDa oligomeric p-tau form (PHF-1) compared to OA treatment alone ( Supplementary Figure 2a, b , Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potent GSK-3 inhibitor, A-107 (Ki=0.6 nM for GSKα and GSK-3β) (59), was selected for the study. OA followed by A-107 treatment showed 23% reduction of 110 kDa oligomeric form band (CP13) and non-significant but partial reduction of the 240 kDa oligomeric p-tau form (PHF-1) compared to OA treatment alone ( Supplementary Figure 2a, b , Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…This effect could be attributed, in part, to the high selectivity and specificity of AR to GSK3β (89) compared to A-107. A-107 display selectivity for both GSK3α and GSK3β (K i = 0.6 nM for both) (90) thereby might dilute the effect of inhibition of GSK3β, which is regarded as the critical kinase in AD (88).…”
Section: Discussionmentioning
confidence: 99%
“…With increased focused development of CNS-intended kinase inhibitors, we anticipate increased reporting of relevant pharmacokinetic properties commensurate with assessing appropriate compartmental exposure. This could include information such as unbound partition coefficient (K pu,u ) data together with confirmation of target engagement with clinical relevance such as PET (Watterson et al, 2013;Prabhakaran et al, 2017;Wager et al, 2017). Indeed, intentionally designed kinase inhibitor candidates for CNS indications exemplified by the LRRK2 and DLK molecules have been reported in the context of detailed DMPK and safety assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse GSK3β inhibitors have been developed and can be grouped according to their mechanism of action and binding affinity: (1) ATP-competitive inhibitors which constitute the largest pool with a diverse range of scaffolds such as SB-216763 and AZD1080 ( Georgievska et al, 2013 ; Li et al, 2015 ). These and other ATP-competitive inhibitors have been shown to exhibit BBB penetrance including pyrazines or oxadiazoles ( Saitoh et al, 2009 ; Onishi et al, 2011 ; Berg et al, 2012 ; Yngve et al, 2012 ; Pandey and DeGrado, 2016 ; Prabhakaran et al, 2017 ). (2) non-ATP competitive inhibitors which either inhibit by binding at a catalytic triad and resisting the correct substrate orientation, such as tideglusib (also known as NP-12) and a thiadiazolidinone derivative (which has shown evidence of brain penetration) ( Luna-Medina et al, 2007 ; Pandey and DeGrado, 2016 ), or by directly competing with the substrate; (3) irreversible inhibitors ( Perez et al, 2009 ); (4) peptide-like inhibitors that act as pseudo-substrates; (5) allosteric inhibitors which bind in non-ATP and non-substrate competitive fashion and thus have potential to enable a more selective and subtle modulation of the enzyme ( Martinez et al, 2002 ; Palomo et al, 2011 , 2017 ) and (6) metal ions such as lithium chloride which has not been included in this review, given that it is neither specific nor potent ( Maqbool et al, 2016 ).…”
Section: Kinase Targets Clinically Assessed For Neurodegenerative Dismentioning
confidence: 99%
“…Probing with total tau DA9 showed that AR treatment caused an adverse effect by increasing the 48 kDa/46 kDa ratio (monomeric tau form; -50%) and reducing the 170 kDa oligomeric form band by 36% ( S2 Fig, Table 3). Another potent GSK-3 inhibitor, A-107 (Ki = 0.6 nM for GSKα and GSK-3β) [69], was selected for the study. OA followed by A-107 treatment showed a 23% reduction of 110 kDa oligomeric p-tau band (CP13), and non-significant, but a partial reduction of the 240 kDa oligomeric p-tau form (PHF-1) compared to OA treatment alone ( S2 Fig, Table 3).…”
Section: Plos Onementioning
confidence: 99%